1978
DOI: 10.1021/ar50131a002
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactions of cyclic imides. Examples of synthetic organic photochemistry

Abstract: Photochemistry in recent years has extended the armamentarium of the organic chemist in coping with synthetic challenges.1 Novel chromophoric systems have been developed and designed, and reactivities of excited states have been defined and utilized. The technique of selective quenching has made possible bond formation and fragmentation leading to molecular structures which would be not readily accessible by recourse to conventional reactions proceeding through ground-state paths.1,2 Probably the most active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…The photochemistry of imides, especially of the N-substituted phthalimides, has been studied intensively by several research groups during the last two decades [233][234][235]. It has been shown that the determining step in inter-and intramolecular photoreactions of phthalimides with various electron donors is the electron transfer process.…”
Section: Aikene-lmidementioning
confidence: 99%
“…The photochemistry of imides, especially of the N-substituted phthalimides, has been studied intensively by several research groups during the last two decades [233][234][235]. It has been shown that the determining step in inter-and intramolecular photoreactions of phthalimides with various electron donors is the electron transfer process.…”
Section: Aikene-lmidementioning
confidence: 99%
“…However, the photoreaction in organic solvents proceeds via the exciplex to give the different cyclized products. Kanaoka electron transfer reaction of S-methyl compounds [70]. In this case, deprotonation from the a-carbon of the S-methyl group in the radical cation occurs to give the S-CH~ radical which cyclizes to give the cyclic thio compounds.…”
Section: ~C Ii=6mentioning
confidence: 99%
“…? 1.6 V) [21][22][23] that have appropriate reduction potentials. In addition, desilylation of benzyl silane radical cations should take place rapidly to form benzyl radicals that can undergo C-C bond forming reactions.…”
Section: Introductionmentioning
confidence: 99%